CHALLENGES AND DAKWAH EFFORTS OF YAKESMA MALUKU DURING THE COVID 19 PANDEMIC - Sayamsuddin Nur; Iin Chandradewi (al-Iltizam: Jurnal Pendidikan Agama Islam, 2022)
This article starts from the phenomenon and problems of the Covid-19 pandemic which ultimately has an impact on various human activities, one of which is da'wah activities which are also hampered due to social restrictions and even prohibitions on carrying out religious activities in mosques for certain times. From here, researchers took the initiative to research da'wah efforts during the Covid-19 pandemic which will focus on the Maluku Branch of Yakesma. This research uses a qualitative approach. The results of the research show that in general, Yakezma does not face serious problems in carrying out its da'wah program during the Covid-19 pandemic, because the da'wah program that has been implemented is not only carried out face-to-face, but they can also carry out These activities are virtual, so that social restrictions and community movement, including restrictions on the use of places of worship resulting from the implementation of PSBB and PPKM policies to break the chain of spread of the corona virus, do not become an obstacle for Yakesma to continue implementing the program. his preaching. Apart from that, Yakesma's efforts in carrying out da'wah activities during the pandemic can be seen from their strategy in packaging their da'wah activities. From the results of data collection carried out by researchers, it shows that before the corona virus had pandemic status, and even before the PSBB and PPKM regulations were implemented, Maluku Yakesma was already running a da'wah program by utilizing digital-based information technology facilities. Yakesnya's da'wah program is carried out livestreaming via YouTube and Facebook and also in the form of short 1 minute videos uploaded to Instagram